2020
DOI: 10.3390/ijms21051751
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Actin-Depolymerizing Factor (ADF) Family Genes and Expression Analysis of Responses to Various Stresses in Zea Mays L.

Abstract: Actin-depolymerizing factor (ADF) is a small class of actin-binding proteins that regulates the dynamics of actin in cells. Moreover, it is well known that the plant ADF family plays key roles in growth, development and defense-related functions. Results: Thirteen maize (Zea mays L., ZmADFs) ADF genes were identified using Hidden Markov Model. Phylogenetic analysis indicated that the 36 identified ADF genes in Physcomitrella patens, Arabidopsis thaliana, Oryza sativa japonica, and Zea mays were clustered into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
(83 reference statements)
5
25
0
Order By: Relevance
“…Analyses of the phylogenetic relationships, gene structures, and encoded motifs indicated that closely related TaADF homologous in the A, B, or D sub-genomes have similar exon–intron structures and encode the same conserved motifs, which is consistent with the results of an earlier study ( Feng et al, 2006 ). Our phylogenetic tree revealed that the ADF genes in the examined monocots are clustered in four main groups, with the ADF genes in the eudicot Arabidopsis distributed in subgroups I, II, and V. The phylogenetic relationships among the ADF genes from selected species were consistent with those described in published reports ( Khatun et al, 2016 ; Huang et al, 2020 ). Accordingly, the ADF genes in the analyzed flowering plants likely evolved from a common ancestor.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Analyses of the phylogenetic relationships, gene structures, and encoded motifs indicated that closely related TaADF homologous in the A, B, or D sub-genomes have similar exon–intron structures and encode the same conserved motifs, which is consistent with the results of an earlier study ( Feng et al, 2006 ). Our phylogenetic tree revealed that the ADF genes in the examined monocots are clustered in four main groups, with the ADF genes in the eudicot Arabidopsis distributed in subgroups I, II, and V. The phylogenetic relationships among the ADF genes from selected species were consistent with those described in published reports ( Khatun et al, 2016 ; Huang et al, 2020 ). Accordingly, the ADF genes in the analyzed flowering plants likely evolved from a common ancestor.…”
Section: Discussionsupporting
confidence: 87%
“…Nine TaADF genes ( TaADF4/5/6/7/8/9/23/24/25 ) were highly expressed in the anther, stigma, and ovary, but were expressed at low levels in the other examined tissues ( Figure 5A ). Similar results were reported for PhADF1/2 in petunia ( Mun et al, 2000 ), SlADF1/2/10/11 in tomato ( Khatun et al, 2016 ), and ZmADF1/2/7/12/13 in maize ( Huang et al, 2020 ). The actin genes in the Arabidopsis genome have been divided into the vegetative class (expressed predominantly in the leaves, roots, stems, petals, and sepals) and the reproductive class (highly expressed in pollen) ( Meagher et al, 1999 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations